2008
DOI: 10.1111/j.1538-7836.2008.02979.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein C supports platelet binding and activation under flow: role of glycoprotein Ib and apolipoprotein E receptor 2

Abstract: Summary.  Background: Activated protein C (APC) regulates thrombin generation and inhibits apoptosis. Endothelial protein C receptor (EPCR)‐bound protein C is activated by thrombomodulin‐bound thrombin. APC inactivates coagulation factors (F)Va/VIIIa and generates cytoprotective signaling downstream of protease‐activated receptor‐1 (PAR‐1). Binding of APC to EPCR both modifies and induces PAR‐1 signaling, but it is unknown if protein C interacts with cells in an alternative manner. Aim: To determine whether pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 32 publications
2
57
1
Order By: Relevance
“…As the assay for cell binding to immobilized APC involved vigorous washing steps, these data do not reflect a simple equilibrium binding reaction, and no definitive conclusion can be drawn regarding receptor-receptor interactions or regarding the energetic contributions of either individual receptor binding to APC. Although no data directly indicate that APC simultaneously binds to both ApoER2 and EPCR, such a situation is not inconsistent with data that suggest that EPCR binds to only APC's N-terminal Gla-domain (46,47) whereas sApoER2 binds to Gla-domain-less APC (19). One possibility is that the distinct APC binding characteristics for Gla-domain-dependent EPCR binding (i.e., fast association) combined with Gla-domain-independent ApoER2 binding (i.e., slow dissociation) allow for the temporal retention of APC on the cell membrane beyond what can be accomplished by either receptor alone.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…As the assay for cell binding to immobilized APC involved vigorous washing steps, these data do not reflect a simple equilibrium binding reaction, and no definitive conclusion can be drawn regarding receptor-receptor interactions or regarding the energetic contributions of either individual receptor binding to APC. Although no data directly indicate that APC simultaneously binds to both ApoER2 and EPCR, such a situation is not inconsistent with data that suggest that EPCR binds to only APC's N-terminal Gla-domain (46,47) whereas sApoER2 binds to Gla-domain-less APC (19). One possibility is that the distinct APC binding characteristics for Gla-domain-dependent EPCR binding (i.e., fast association) combined with Gla-domain-independent ApoER2 binding (i.e., slow dissociation) allow for the temporal retention of APC on the cell membrane beyond what can be accomplished by either receptor alone.…”
Section: Discussionmentioning
confidence: 65%
“…Previously, by using a non-equilibrium binding method, we showed that APC binds to sApoER2 immobilized on a microtiter plate (19). Here we used the equilibrium binding method of surface plasmon resonance (SPR) analysis to compare parameters for APC binding to sApoER2 and to sEPCR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Although platelets do not possess an equivalent for the EPCR, a recent report indicated that immobilized protein C (PC) or activated protein C (APC) support platelet adhesion and activation through mechanisms that could involve GPIb␣. 48 The latter finding indirectly suggests that platelets may at least express receptors that could mediate interactions with APC. In our studies, an excess of recombinant human APC in the incubation media inhibited up to 30%, but never completely pageed the rFVIIa association with platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other PAR3-effector interactions are required for signal induction, diversification, and regulation ( Figure 3). PAR-effector complexes are hypothesized to involve the formation of PAR-PAR heterodimers and homodimers, 43 which may enable PARinduced transactivation of other PARs, integrate the transactivation of other GPCRs such as S1P1, 18,25,26 and incorporate cooperative cross talk with integrins such as Mac1 44,45 or other receptors such as ApoER2 46,47 or Tie2. 20,42,48 Formation of these complexes may achieve a signaling bias by promoting or discouraging the association of particular G-protein ensembles, 49,50 by recruiting b-arrestins, 30 or by incorporating nontraditional PAR signaling pathways via transactivations such as the activation of Tie2 by noncanonical activation of PAR3.…”
mentioning
confidence: 99%